Effect of crop geometries and fertility levels on growth, yield and residual nutrients of cotton (Gossypium hirsutum) hybrids under rainfed condition* - SHUKLA, U N; KHAKARE, M S; SINGH, SMITA; VERMA, S K (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during kharif season of 2008-09 to study the effect of crop geometries and fertility levels on growth, yield and residual nutrients of cotton (Gossypium hirsutum L.) hybrids under rainfed condition. Cotton hybrids MLCH 318 was planted under wider crop geometry of 90 cm × 60 cm which recorded significantly higher growth parameters, monopodial branches and seed cotton weight/plant. However, yield potential of MLCH 318 were higher under closer crop geometry (60 cm × 60 cm) and recorded significantly taller plant, yield attributes and yield of cotton over wider crop geometry of 90 cm × 60 cm (S1) due to more number of plants stand at initial and harvest stages, respectively. Although, cultivar VBCH 2231 (V2) with crop geometry of 90 cm × 60 cm (S1) recorded more in residual status of N (200.44 and 204 kg/ha), P (16.82 and 16.67 kg/ha) and K (496.50 and 489.04 kg/ha), respectively. Among fertility levels, growth characters, yield attributes and yield of cotton with residual N (204.11), P (17.24) and K (495.26 kg/ha) were significantly higher under highest levels of fertility, i.e. 62.5: 31.25: 31.25 kg N: P: K/ha. Thus, it concluded that sowing of cultivar MLCH 318 at crop geometry of 60 cm × 60 cm and fertilized with. 62.5: 31.25: 31.25 kg N: P: K/ha produced significantly higher yield attributes and yield under rainfed condition.